Effect of Substitusion of Tubifex sp.With Artificial Food On Growth and Survival Rate OfLele Mutiara Larvae (Clarias gariepinus Burchell, 1822) - Rudy Julius Simanjuntak; Netti Aryani; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT                          This research aimed to determine the effect of substitusion of Tubifex sp. with artificial food on growth and survival rate of Lele Mutiara larvae. This research was conducted from November 2018 - January 2019 at Fish Hatchery and Breeding Laboratory, Fisheries and Marine Science Faculty of Riau University. The method used is an experimental method with a Completely Randomized Design (CRD) with four treatments and three replications. The treatments were P1 (Tubifex sp. 40 days), P2 (Artificial Food 40 days), P3 (Tubifex sp. 30 days + Artificial Food 10 days), P4 (Tubifex sp. 20 days + Artificial Food 20 days), and P5 (Tubifex sp. 10 days + Artificial Food 30 days). The subjects used in this research were 4 day old Lele Mutiara larvae. The research process was conducted by raising Lele Mutiara larvae in an aquarium containing 15 liters of water with a stocking density of 2 fish/liter for 40 days. Frequency of feeding that conducted was four times a day as much as 50% of the weight of biomass. The result showed that P3 (Tubifex sp. 30 days + Artificial Food 10 days) was the highest growth (2,20 g, 6,27 cm, and 16,79%/day), the best feed efficiency was 58,23%, and the highest survival rate was 92,22%. Keywords :Lele Mutiara Larvae;Tubifex sp., Artificial Food,Survival Rate